ANALISA PENERAPAN BIAYA STANDAR SEBAGAI ALAT PENGENDALIAN BIAYA PADA NIPPON STEEL BLUESCOPE INDONESIA-CILEGON - Pohan, Erlina Sari; Putri, Dea Irena (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
This study aims to examine Analysis Of Application Of Standard Costs As A Cost Control Tool of the PT. Nippon Steel BlueScope Indonesia-Cilegon. The research method taken is descriptive qualitative method, which is a research that describes the characteristics of the problems related to the characteristics of the subject under study. This research emphasizes the understanding of the application of standard cost as a tool of cost control at PT. Nippon Steel BlueScope Indonesia.The result of this study indicate that PT. NSBI in applying raw material cost standard is with market offer or historical cost and also apply upper. Application of standard cost of raw materials at PT. NSBI is one of the tools or tools used by PT. NSBI in the process of cost control or saving program, the standard cost applied has functioned well, this is evidenced by the variant produced by some PT products. NSBI between the standard cost and the actual cost of only one product suffered from a poor difference, so the application of standard cost is a fairly accurate benchmark for use in the production process.